Thomas W. Gallant, Modern Greece: from the War of Independence to the Present - Doumanis, Nicholas (Historein, 2018)
Thomas W. Gallant. Modern Greece: from the War of Independence to the Present. 2nd ed. London and New York: Bloomsbury, 2016. xxi + 354 pp.